2015
DOI: 10.1063/1.4930593
|View full text |Cite
|
Sign up to set email alerts
|

Tunnel junction enhanced nanowire ultraviolet light emitting diodes

Abstract: Polarization engineered interband tunnel junctions (TJs) are integrated in nanowire ultraviolet (UV) light emitting diodes (LEDs). A ∼6 V reduction in turn-on voltage is achieved by the integration of tunnel junction at the base of polarization doped nanowire UV LEDs. Moreover, efficient hole injection into the nanowire LEDs leads to suppressed efficiency droop in TJ integrated nanowire LEDs. The combination of both reduced bias voltage and increased hole injection increases the wall plug efficiency in these d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 26 publications
1
51
0
Order By: Relevance
“…Further, given the low cost of Si substrate, the majority of studies of group-III nitride nanowire UV LEDs are on Si substrate. These nanowire LED structures are primarily grown by MBE (through a spontaneous formation process, as afore-discussed), and predominantly with AlGaN ternary nanowires [25,36,37,51,[65][66][67][68][69]. The relatively longer history of investigating the MBE growth of AlGaN nanowires on Si, compared with the growth on other foreign substrates, has also made AlGaN nanowire UV LEDs on Si of better performance compared with devices on other foreign substrates, albeit with various limitations of using Si substrate (see Section 4).…”
Section: Algan Nanowire Uv Leds On Simentioning
confidence: 99%
“…Further, given the low cost of Si substrate, the majority of studies of group-III nitride nanowire UV LEDs are on Si substrate. These nanowire LED structures are primarily grown by MBE (through a spontaneous formation process, as afore-discussed), and predominantly with AlGaN ternary nanowires [25,36,37,51,[65][66][67][68][69]. The relatively longer history of investigating the MBE growth of AlGaN nanowires on Si, compared with the growth on other foreign substrates, has also made AlGaN nanowire UV LEDs on Si of better performance compared with devices on other foreign substrates, albeit with various limitations of using Si substrate (see Section 4).…”
Section: Algan Nanowire Uv Leds On Simentioning
confidence: 99%
“…86 In this regards, Myers's group realized n+ graded-AlGaN/AlGaN-quantum-disks/p+ garded-AlGaN with a bottom p-GaN/InGaN/n-GaN tunnel junction embedded on top of an n-type silicon, whereas the graded-AlGaN structures are used for inducing the respective polarization-induced doping. 32 The interband tunneling at the tunnel junction allows the electron injection into the n-GaN layer and holes into the graded p-AlGaN layer. As a result, tunnel junction LED showed reduced operating voltage and increased injection current.…”
Section: Tunnel Junction and Inverted P-i-n Structuresmentioning
confidence: 99%
“…b). Alternatively, a high work function metal or commonly used n‐type silicon wafer integrated with tunnel junction can be used . For the current study, we utilize the simplified structure shown in Fig.…”
Section: Experimental and Simulation Detailsmentioning
confidence: 99%